Blood lipid profile study in patients with acute stroke - AL-Bayatti, Ansam A.; Gadeer, widadk A.; Mahmoud, Hayder N. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: The accumulation of the lipid in the vascular smooth muscle cell within the arterial intima is a key process of the pathogenesis of atherosclerosis. Atherosclerosis is a degenerative disease of blood vessels leading to stroke.Materials & Methods.One hundred and ten patients with acute stroke were included in this study 88 patients with ischaemic or infarction stroke and 22 patients with hemorrhagic type ) as well as thirty apparently normal healthy subjects as controls.Results.Triglycerides levels and AI only were statistically significant in ischaemic type of stroke (P